Remediating Vertov: Man with a movie camera phone. Issue 1 (1st October 2013) - Keep, Dean; Berry, Marsha
Using Džiga Vertov's seminal experimental film Man with a Movie Camera (Vertov, 1929), as the central text for this practice-led research, the authors have produced short experimental video works that explore cities through the lens of the mobile phone-camera. In this article the authors investigate the creative possibilities of camera-phone technology, and how in turn these technologies may extend or give rise to new modes of experimental and/or hybrid cinematic forms. With particular reference to the authors' mobile videos (Spatial Threshold and Lifts), this article discusses the aesthetics, constraints and opportunities presented by camera-phone technologies and how these factors may influence the production of experimental mobile video.